The capacity of potential attachment is central to the formation of working alliance in Psychotherapy: A Grounded Theory - Abbasi, Fatemeh; Ali Goodarzi, Mohammad; Mazidi, Mohammad; Reza Sarafraz, Mehdi (International Journal of Psychosocial Rehabilitation, 2021)
The main objective of this study was to explore the dynamics of working alliance during the prerecorded psychotherapy sessions using a grounded theory paradigm. To collect the data, fifteen psychotherapeutic pre-recorded videos were selected based on theoretical sampling procedures. Three coders were trained to extract initial open codes related to the working alliance phenomenon after they watched psychotherapeutic videos. We encoded the data in three stages of open, axial and selective coding through deductive and inductive methods. In the final stage, we used a paradigm coding strategy to develop our grounded theory of working alliance. The ground theory indicates that “reflective functioning” (causal condition), in interaction with “rapport and goal setting” (context) and “resistance” (intervening condition) “engages the client and psychotherapist in “learning process” (action/interaction strategies) which in turn activates the appropriate or non-appropriate patterns of attachment of both client and psychotherapist. These interactions, in turn, exert its direct influence on the formation or disruption of working alliance (consequences). These five elements are involved in the formation of working alliance during any type of psychotherapy regardless of the psychotherapy approach and the capacity of potential attachment is central to the model.